E-Learning Model for Problem Based Learning on Heat and Thermodynamic Topics in High School - Fauzi Bakri; Sunaryo Sunaryo; Velinda Finka Irawan; Dewi Muliyati (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2018)
The development of information and communication technology (ICT) in the 21st century makes it easier for students to be more active in the learning process. Physics learning materials are needed to support the problem-based learning process in high school. This study aims to produce e-learning models for problem-based learning on Heat and Thermodynamics topics. The result shows media can be used in learning in high school class XI. We uses the research and development method, with the Dick and Carey model. The study was conducted in a digital media laboratory, Physics Education Department of Universitas Negeri Jakarta from January to June 2018. E-Learning models have been produced for problem-based learning in the topic of Heat and Thermodynamics. This WordPress-based E-Learning model can display physics material enriched with images, graphics, animations, simulations, and videos. Students are facilitated to understand the concepts learned. The e-learning model is equipped with assessment tools that can be used online. Students are facilitated to learn independently without limited space and time. The E-learning model developed was also equipped with discussion groups in the form of chats for all registered users. The media validation obtained the results of system evaluation, content, and e-learning infrastructure with 78.9 points average. The material validation gives an 81.55 rating. Concerning media and material, e-learning media is declared feasible as a medium for self-learning. The e-learning model for problem-based learning is feasible to use to train the ability to critical thinking, creative thinking, collaborative, and communicate for students in high school.